1997
DOI: 10.1200/jco.1997.15.8.2780
|View full text |Cite
|
Sign up to set email alerts
|

Phase I/II study of idarubicin given with continuous infusion fludarabine followed by continuous infusion cytarabine in children with acute leukemia: a report from the Children's Cancer Group.

Abstract: This combination is active in patients with relapsed or refractory AML. The major toxicity encountered is hematologic. This regimen may be useful therapy for AML and should be compared with standard induction therapy in children with newly diagnosed AML.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 4 publications
0
25
0
Order By: Relevance
“…Clinical studies of fludarabine phosphate with topo-II inhibitors have been carried out against leukemia and lymphoma. [19][20][21][22] In our study, 2-F-ara-A in combination with doxorubicin showed additive effects for three cell lines and Leukemia synergistic/additive effects for one cell line, while 2-F-ara-A in combination with etoposide showed additive effects in all four cell lines. These findings suggest that the simultaneous administration of fludarabine phosphate with doxorubicin or etoposide would have the expected activity.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Clinical studies of fludarabine phosphate with topo-II inhibitors have been carried out against leukemia and lymphoma. [19][20][21][22] In our study, 2-F-ara-A in combination with doxorubicin showed additive effects for three cell lines and Leukemia synergistic/additive effects for one cell line, while 2-F-ara-A in combination with etoposide showed additive effects in all four cell lines. These findings suggest that the simultaneous administration of fludarabine phosphate with doxorubicin or etoposide would have the expected activity.…”
Section: Discussionmentioning
confidence: 83%
“…The clinical study of the fludarabine phosphate/cytarabine sequence produced a high response rate. 16,17,21 The decreased cellular deoxynucleotide concentration due to the inhibition of ribonucleotide reductase by 2-F-ara-ATP is associated with an increase in the rate of cytarabine phosphorylation by deoxycytidine kinase. 16,27 This is considered to be the major mechanism of the synergistic interaction of sequential exposure to 2-F-ara-A or fludarabine phosphate followed by cytarabine.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14][15] Since in vitro studies have shown a two-to three-fold increase of ara-CTP levels in AML and CLL blasts, 16 and ALL in adults and children. [18][19][20][21][22][23] Data on intracellular ara-C metabolism under these regimens are rare. 18 Notwithstanding the large number of in vitro studies, F-ara-A has never been tested systematically as a modifier of ara-C toxification in different subtypes of acute leukemia, especially in lymphoblastic cells.…”
Section: Introductionmentioning
confidence: 99%